End User Computing Satisfaction Gereja Digital dan Partisipasi Jemaat (Studi Pada Aplikasi Gereja GBI Keluarga Allah) - Arini Adiputri (Jurnal Indonesia Sosial Sains, 2022)
This study aims to analyze end user computing satisfaction on the GBI Keluarga Allah’s application and its impact on congregational participation in worship, growth in the cell community and church ministry. In this case, end user computing satisfaction is measured by five indicators, it is content, accuracy, format, timeliness and ease of use of the application. In this study, 100 questionnaires were distributed and the final sample obtained was 97 respondents, who are members of the GBI Keluarga Allah who use GBI KA application. The results of the analysis show that the end user computing satisfaction of the GBI Keluarga Allah congregation is quite high and affects the level of participation of the congregation in worship. This end user computing satisfaction also affects the participation of the members of the GBI Keluarga Allah in participating in cell groups and services, although there are other factors that affect the level of participation of the congregation in these cell groups and services besides the end user computing satisfaction of the congregation on the application of GBI Keluarga Allah.